Một số vấn đề cơ bản đổi mới cơ chế quản lý vật tư - Vũ, Quang Anh (2011)
Tác giả: Vũ Quang Anh, PTS; Nguyễn Khắc Tiệm; Đinh Văn Tiến; Trần Thanh Sơn; Vũ Thế Bằng; Lê Quang Duệ; Phạm Văn Trọng; Hoàng Mạnh Đức; Mai Liên -- Từ khóa: Đổi mới cơ chế ; Vật tư; Quản lý vật tư; Cơ chế quản lý